A study on implementation of WHO labour care guide in low-risk pregnant women and its impact on maternal and perinatal outcome - N., Srividya; Lakshmi M., Sri Jhansi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: WHO Labour Care Guide is a labour monitoring tool that is developed to support respectful maternity to provide positive childbirth experience with evidence-based recommendations. Methods: This is an observational study comparing WHO labour care guide with WHO modified partograph in low-risk pregnant women who are in active phase of labour. The study included 80 labouring women who are divided into two groups with 40 participants in each group. In group 1 WHO modified partograph was used and in group 2 WHO labour care guide was used as a tool to assess the course of labour. Maternal and perinatal outcomes were analysed for both the groups. Results: There is no significant difference in the caesarean section rates and instrumental deliveries between the two groups. There is a rise in the incidence of PPH and meconium-stained liquor in group 2 compared to group 1. None of the participants had labour beyond 12 hours. NICU admissions were higher in group 2. Conclusions: In our study, the WHO modified partograph was found as equivalent to WHO labour care guide in identifying prolonged labor. Also, maternal and perinatal outcomes were equally identified by both types of partograph. WHO labour care guide did not prove to be beneficial over WHO modified partograph in terms of maternal and perinatal outcomes in Indian parturient women.